The Use of Curse Tablets among Slaves in Rome and its Western Provinces. - Alvar-Nuño, Antón (Mohr Siebeck, 2020)
During the 1960s, in the hey-day of slave-studies, it was generally considered that in Roman antiquity slaves resorted to malign magic to curse their masters, using techniques learned from wandering astrologers who visited the household. This notion drew indirectly upon the Marxist discourse of class-struggle and also took for granted that there was a specific 'religion of slaves' that was significantly different from what was taken to be 'Roman religion'. More recently, it has been argued that recourse to writing curses by slaves should be understood in postcolonial terms as a form of group-resistance to the dominant power. A close analysis of surviving curse texts, however, suggests that neither of these positions is convincing. The present contribution focuses not on the motives that slaves might have had in writing a curse but, rather, on the access they may have had to this particular dispositif. The argument is that slaves resorted in this area to what they understood as local practice.
https://www.mohrsiebeck.com/en/service/rights-permissions/
Keywords: Esclavos - Roma; Esclavitud; Conflicto social; Magia - Roma; Curse tablets